2007 3rd International IEEE/EMBS Conference on Neural Engineering 2007
DOI: 10.1109/cne.2007.369660
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Bioimpedance Cerebral Monitoring. A Study of the Current Density Distribution and Impedance Sensitivity Maps on a 3D Realistic Head Model

Abstract: Abstract-There have been several studies of the application of electrical bioimpedance technology for brain monitoring in the past years. They have targeted a variety of events and injuries e.g. epilepsy or stroke. The current density distribution and the voltage lead field associated with an impedance measurement setup is of critical importance for the proper analysis of any dynamics in the impedance measurement or for an accurate reconstruction of an EIT image, specially a dynamic type. In this work for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…These assessments allowed us to highlight the contributions of the white matter, gray matter, and CSF in the distributions of current through the brain parenchyma. The large contribution of the CSF was in agreement with previous studies 47 and suggested that changes in the CSF influence the total distribution of currents in the head, i.e., the shunting effect between the skull and CSF. 48 Hence, excluding the CSF from the model, as some simulation-based studies do, 32 deviates such numerical studies from real case scenarios.…”
Section: Discussionsupporting
confidence: 80%
“…These assessments allowed us to highlight the contributions of the white matter, gray matter, and CSF in the distributions of current through the brain parenchyma. The large contribution of the CSF was in agreement with previous studies 47 and suggested that changes in the CSF influence the total distribution of currents in the head, i.e., the shunting effect between the skull and CSF. 48 Hence, excluding the CSF from the model, as some simulation-based studies do, 32 deviates such numerical studies from real case scenarios.…”
Section: Discussionsupporting
confidence: 80%
“…, F. Seoane et al 2007b. Recent simulations with a realistic model have shown that the effect of the skull is less shielding than earlier believed (F. Seoane et al 2007b), and it has been shown that the current density distribution depends largely on the electrical properties of each specific tissue. A smaller current density in the intracranial structures is explained not only by the shielding layer of low conductive bone.…”
Section: Effect Of the Skullmentioning
confidence: 90%
“…Seoane et al [19] also studied electrical bioimpedance cerebral monitoring in a 3D numerical model of the head. They calculated the current density distribution and impedance sensitivity maps on a head model with resolution down to 1 mm.…”
Section: Simulations On a Numerical Head Phantommentioning
confidence: 97%
“…On the contrary, in the present study, measurements at radius less than 2.5 cm from an injection position were prevented, due to higher expected errors in this region. Seoane et al [19] also compared the sensitivity maps of three different electrode configurations using three different current frequencies, while in the present study, only one current frequency (of 50 kHz) was used with many four-electrode configurations, optimizing for a specific criterion -the best sensitivity to the stenosis degree of the chosen LMCA segment.…”
Section: Simulations On a Numerical Head Phantommentioning
confidence: 98%
See 1 more Smart Citation